2018
DOI: 10.3390/met8050321
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Valuable Metals from Lithium-Ion Batteries NMC Cathode Waste Materials by Hydrometallurgical Methods

Abstract: The paper focuses on the improved process of metal recovery from lithium-ion batteries (LIBs) lithium nickel manganese cobalt oxide (NMC) cathode waste materials by using hydrometallurgical methods. In the acid leaching step, the essential effects of acidity concentration, H 2 O 2 concentration, leaching time, liquid-solid mass ratio, and reaction temperature with the leaching percentage were investigated in detail. The cathode material was leached with 2M H 2 SO 4 and 10 vol. % H 2 O 2 at 70 • C and 300 rpm u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(53 citation statements)
references
References 47 publications
(46 reference statements)
2
44
0
1
Order By: Relevance
“…The inorganic acids present a satisfactory performance during leaching and achieve higher efficiency of metal extraction than organic acids [29]. Techniques that are used to prepare the final products from the leaching filtrate include solvent extraction [10,[30][31][32][33], electrochemical techniques [34][35][36], selective precipitation [21,[37][38][39][40], and co-precipitation [41][42][43]. Among these, co-precipitation is the most efficient technique for the recovery of more than one metal (mixed metal) due to a higher level of homogeneity and spherical/sphere-like products [44].…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic acids present a satisfactory performance during leaching and achieve higher efficiency of metal extraction than organic acids [29]. Techniques that are used to prepare the final products from the leaching filtrate include solvent extraction [10,[30][31][32][33], electrochemical techniques [34][35][36], selective precipitation [21,[37][38][39][40], and co-precipitation [41][42][43]. Among these, co-precipitation is the most efficient technique for the recovery of more than one metal (mixed metal) due to a higher level of homogeneity and spherical/sphere-like products [44].…”
Section: Introductionmentioning
confidence: 99%
“…The sulphate solutions came from a recycling LIBs waste cathode materials, which were done by previous research; their content is shown in Table 1 [18]. Sodium carbonate (Na 2 CO 3 ) was purchased from Nihon Shiyaku Reagent, Tokyo, Japan (NaCO 3 , 99.8%), for the chemical precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…The metals cobalt, nickel, copper, manganese, and iron bear an outstanding position in the recycling of LIBs due to their high intrinsic value and the comparatively low cost of recovery [56]. Here, pyrometallurgy can be combined with hydrometallurgical processes but pure hydrometallurgical processing is becoming more and more important [39,58,97,98]. When discussing different metallurgical technologies for the processing of spent LIBs, the pyro-and hydrometallurgical unit processes are compared as stand-alone.…”
Section: Metallurgymentioning
confidence: 99%
“…Once dissolved, the metals are extracted from the solvent by liquid-liquid extraction, ion exchange, or chemical precipitation [69,77,97]. If the resulting metal salts meet the quality requirements of the corresponding raw materials, subsequent recovery can be forgone.…”
Section: Hydrometallurgymentioning
confidence: 99%